The effect of interfacial layer on the performance of organic light-emitting diodes - Choulis, Stelios A.; Choong, Vi-En; Mathai, Mathew K. (My University, 2005)
We demonstrate high efficiency organic light-emitting devices by incorporation of a nanoscale interfacial layer between a hole-conducting layer (PEDOT:PSS) and a light-emitting polymer layer (LEP) to improve hole injection. The interfacial layer has appropriate highest occupied molecular orbital level in order to act as a bridge for efficient hole injection from the PEDOT:PSS into the LEP. As an example we have incorporated a suitable interfacial layer into a green-emitting single-layer electrophosphorescent light-emitting diode. Devices with the interfacial layer show a peak efficiency of 41 lm/W, an improvement of more than 25% in their performance over comparable devices without the interfacial layer. The results presented here introduce a novel method to improve hole injection and thus efficiency in organic electroluminescent devices
Keywords: Light emitting diodes; Polymers; Electroluminescence